Adverse events of ursodeoxycholic acid: a real-world pharmacovigilance study using FAERS (2004–2023) - Ni, Yahui; Guan, Xin; Gao, Xiaoxue; Wang, Ya; Qin, Dongyuan; Shan, Zhangtao; Wang, Na (Frontiers in Medicine, 2025)
BackgroundUrsodeoxycholic acid (UDCA) has been widely used in the treatment of hepatobiliary disorders and its clinical application is more and more extensive. However, to our knowledge, there are currently no clinical and scientific studies on the safety of UDCA based on large populations. In this study, UDCA-related adverse events (AEs) were evaluated through data mining based on the FDA Adverse Event Reporting System (FAERS) database.MethodsThe AE reports induced by UDCA as the primary suspected drug were extracted from the FAERS database. Disproportionality analysis was performed to explore potential AE signals of UDCA using four robust algorithms, including reporting odds ratio (ROR), the proportional reporting ratio (PRR), the Bayesian confidence propagation neural network (BCPNN), and the Empirical Bayesian geometric mean (EBGM). The difference in UDCA-associated AE signals was also investigated concerning sex.ResultsA total of 1,651 AEs were identified to be associated with UDCA. Common AEs consistent with the drug insert included diarrhea or loose stools, right upper abdominal pain, rash, and so on. Several unexpected AEs, such as interstitial lung disease and pancytopenia, were also identified. UDCA-related AEs affected 27 system organ classes (SOCs), and the signal intensity showed gender differences.ConclusionThis study investigated AEs associated with UDCA in both SOC and preferred terms (PTs) levels, providing valuable insights to the comprehensive landscape of AEs caused by UDCA. The results of this study help optimize the clinical use of UDCA and reduce its potential side effects, promoting its safe use in clinical application.